Looking at what we cannot see. Essay on poetics of the distance in the scenic practices of Lia Rodrigues and Antônio Araújo (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In addition to a set of buildings, what is inherited from the Italian Renaissance theater is an architecture of the gaze. Leaving the Aristotelian logic of this model means exploring other ways of conceiving and organizing the visible, one of which, and the one we are going to explore, is based on the distance relations between bodies. To this end, the essay focuses on scenic experiences conceived by Lia Rodrigues and Antônio Araújo, and questions how they make us perceive the invisible.
Keywords: Italian renaissance theater; Perception of space; Visual attention; Informal space; Presence; Proxemics